Stability and reactivity of dinuclear iron(III)-salen complexes as catalysts in ethylene polymerization: A computational approach - Ahmed Olalekan Omoniyi; Saratu Mamman; Adiat Ibironke Arogundade; Pius Onyeoziri Ukoha; Yuanfeng Wu (Results in Chemistry, 2023)
The increasing demand for olefin polymers has prompted extensive research on catalysis, processes, and structural characterization to explore their economic potential. In this study, N,N'-bis(salicylidene)-1,2-ethylenediamine (salen) was synthesized, complexed with Fe(III) ion, and the complex was bridged by simple condensation reaction with five different dicarboxylic acids to produce dinuclear complexes. Different methods, such as 1H NMR, FT-IR, UV–Vis, and EDX elemental analysis, were used to analyze and identify the ligand and complexes. Spectroscopic results supported by molecular modeling studies, revealed that the complexes had an octahedral geometry. Structural optimization of the ligand and metal complexes was performed using Avogadro (version 1.2.0) and the Universal Force Field molecular mechanics level. Density functional theory was used to conduct computational calculations on the stability and reactivity of the zeolite-supported and unsupported complexes as catalysts for the polymerization of ethylene. Interestingly, the supported complexes were found to exhibit lower stability and higher reactivity than the neat metal complexes. As such, the synthesized complexes are promising catalysts for the production of polyethylene, and their use could significantly reduce the cost of industrial polyethylene production.